Technology transfer within MNEs: inter-subsidiary competition and cooperation - Li, Dan (2009)
Much theory and research that seeks to explain why and how technology transfers occur within multinational enterprises (MNEs) actually addresses the question of how these transfers occur among cooperative subsidiaries, and relies on the assumption of inter-subsidiary cooperation. However, subsidiaries do not always cooperate. We suggest that the success of technology transfer among subsidiaries depends on the extent to which the relationships among an MNE's subsidiaries (i.e. inter-subsidiary) are competitive or cooperative. Inter-subsidiary cooperation is determined by the MNE's international strategy, organizational structure, and the social relationships among subsidiaries. Both hierarchical and social relational factors drive the potential for inter-subsidiary multimarket competition that originates from the overlap on the subsidiaries' products, technologies, and market portfolios.